Humane entrepreneurship: Some steps in the development of a measurement scale. (4th May 2021) - Parente, Roberto; El Tarabishy, Ayman; Botti, Antonio; Vesci, Massimiliano; Feola, Rosangela
ABSTRACT: Humane entrepreneurship (HumEnt) is a new model of entrepreneurship in which the attention that firms have traditionally paid to business is integrated with care for the following: firm members, the planet, and society at large. The goal of this article is to address some preliminary issues to develop a measurement scale to validate firm humane entrepreneurial orientation (HEO). The articles defines HEO beginning with the review of the main literature in terms of its three components: entrepreneurial orientation (EO), sustainable orientation (SO), and humane resource orientation (HRO). The article thereby makes some contributions with regard to how and at which organizational level the components of HEO can be measured.